Pain evoked by polymodal stimulation of hand veins in humans. - Arndt, J O (1991)
1. To explore the function of the sensory innervation of veins in humans we used a psychophysical approach to study painful and non-painful sensations by applying polymodal stimuli (electrical, stretch, cold/heat and osmotic) inside vascularly isolated hand vein segments before and after blockade of either venous or cutaneous afferents. 2. All modes of stimulation elicited pain, which showed only slight adaptation during 10 min of maintained stimulation. Pain increased monotonically with stimulus intensity between threshold and the maximally tolerable pain. 3. The exponents of the power functions of the pain magnitude-stimulus strength relations for five stimulus modes ranged between 2.5 and 3.3 but did not significantly differ from one another (P = 0.3). 4. Pain evoked by all stimuli was reported to be of similar quality, i.e. sharp, aching and unpleasant; it was accompanied by non-painful sensations (skin movements on stretching, warm and cold sensation with intravenous thermal stimulation) unless the skin above the stimulated vein segment was numbed with benzocaine ointment. 5. Pain could no longer be evoked in the presence of 0.4-0.8% procaine within the stimulated vein segment. 6. These observations are consistent with the view that veins are invested with polymodal nociceptors only, which in all likelihood are connected with thinly myelinated afferents of the A delta group. 7. The vascularly isolated vein segment may open a new avenue for pain research in humans.